Community Infrastructure Development Planning towards Rural Development in Sarawak - Peter Aning Tedong; Mark Anak Edward Tuah; Melasutra Md. Dali (Penerbit UTHM, 2024)
The development of community infrastructure is essential for a region and its community’s socio-economic growth. This book adopts the qualitative approach by case study design with Song District, Sarawak as the study area, involving methods that included in-depth interviews with multiple key actors in the government and communities and direct observation to examine the community infrastructure planning in Sarawak. Based on a study carried out in Song District, Sarawak, the book findings shows that although there has been progress in the district’s development of community infrastructure, there were a number of challenges to delivering community to certain locations within the district, in addition to satisfying the community needs. The book reveals several challenges of the community infrastructure planning process namely influence of geographical factor, management of financial resources, cooperation and collaboration of stakeholders and community involvement. In terms of governance, the study highlights that governments at all levels needs to be aware of their responsibilities, utilising networks and collaborations with other agencies and community to enhance local decision-making in developing community infrastructure in rural areas. In sum, the book suggests that the presence of strong institutional actors and coordination involving government at all levels and community is important in dealing with the many challenges and governing a successful community infrastructure delivery to fulfill the needs of the rural community. Consequently, this book also recommended some improvements on the approach and mechanisms governing the rural community infrastructure planning in Sarawak.